Educational needs of healthcare professionals and members of the general public in Alberta Canada, 2 years after the implementation of medical assistance in dying. (31st May 2019) - Wilson, Donna M.; Triscott, Jean A. C.; Cohen, Joachim; MacLeod, Rod
Abstract: Medical assistance in dying (MAID) was implemented across Canada in June of 2016, after each Canadian province and territory had developed their own MAID processes. Over the first 2 years, just under 300 Alberta citizens received MAID services, a very small proportion (<0.5%) of all 52, 000 decedents. An online 2017–2018 survey of Alberta healthcare providers and members of the general public was conducted to assess and compare their knowledge of MAID. A devised brief survey tool was posted online, with broad‐based advertising for voluntary participants. The survey was taken down after 282 Albertans had participated (100+ healthcare professionals and 100+ members of the general public), a non‐representative sample. Through SPSS data analysis, educational needs were clearly evident as only 30.5% knew the correct approximate number of MAID deaths to date, 33.0% correctly identified the point in life when MAID can be done, 48.9% correctly identified the locations where MAID can be performed, 49.3% correctly identified who can stop MAID from being carried out, and 52.8% correctly identified how MAID is performed to end life. Healthcare professionals were significantly more often correct; as were participants born in Canada, university degree holders, working persons, those who identified a religion, had experience with death and dying care, had direct prior experience with death hastening, thought adults had a right to request and receive MAID, had past experience with animal euthanasia, and had hospice/palliative education or work experience. Age, gender, and having previously worked or lived in a country where assisted suicide or euthanasia was performed were not significant for educational needs. These findings indicate new approaches to meet sudden assisted suicide educational needs are needed.